2012
DOI: 10.1155/2012/168602
|View full text |Cite
|
Sign up to set email alerts
|

Differential Proteome Profiling Using iTRAQ in Microalbuminuric and Normoalbuminuric Type 2 Diabetic Patients

Abstract: Diabetic nephropathy (DN) is a long-term complication of diabetes mellitus that leads to end-stage renal disease. Microalbuminuria is used for the early detection of diabetic renal damage, but such levels do not reflect the state of incipient DN precisely in type 2 diabetic patients because microalbuminuria develops in other diseases, necessitating more accurate biomarkers that detect incipient DN. Isobaric tags for relative and absolute quantification (iTRAQ) were used to identify urinary proteins that were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 43 publications
3
33
0
Order By: Relevance
“…Interestingly, elevation of CP and ORM1, which predicts development of high albuminuria (Fig. 6B), is detected earlier in plasma than in urine in view of the fact that a recent study homologous carried out by Gonzalez-Calero et al found elevated urine CP in individuals with de novo high albuminuria (data submitted), as well as a previous study that found higher urine levels of ORM1 in diabetic patients with high albuminuria [30]. Our results suggest that routine analysis of the plasma levels of the hereby reported proteins by turdibimetry could be useful to evaluate renal function in hypertensive patients with no clinical signs of renal impairment.…”
Section: Discussionsupporting
confidence: 66%
“…Interestingly, elevation of CP and ORM1, which predicts development of high albuminuria (Fig. 6B), is detected earlier in plasma than in urine in view of the fact that a recent study homologous carried out by Gonzalez-Calero et al found elevated urine CP in individuals with de novo high albuminuria (data submitted), as well as a previous study that found higher urine levels of ORM1 in diabetic patients with high albuminuria [30]. Our results suggest that routine analysis of the plasma levels of the hereby reported proteins by turdibimetry could be useful to evaluate renal function in hypertensive patients with no clinical signs of renal impairment.…”
Section: Discussionsupporting
confidence: 66%
“…Data were normalized for loading error by bias and the background correction was calculated using the Pro Group™ algorithm (ABSciex). To determine the cutoff value for significant fold changes, coefficient of variation and cumulative frequency were calculated for the common proteins employing the R statistical package58. Using this tool, we considered statistically significant only those changes with a p value ≤ 0.05 and a ratio ≥ 1.4 (or ≤0.7).…”
Section: Methodsmentioning
confidence: 99%
“…The use of this powerful technique is gradually becoming the method of choice in the field of biomarker discovery [3, 7678]. This method allowed discovering P- and E-cadherins as urinary biomarkers of idiopathic nephrotic syndrome [76].…”
Section: 2 Isobaric Tags For Relative and Absolute Quantitation (Itraq)mentioning
confidence: 99%